Aerosol climatology and planetary boundary influence at the Jungfraujoch analyzed by synoptic weather types - M. Collaud Coen; E. Weingartner; M. Furger; S. Nyeki; A. S. H. Prévôt; M. Steinbacher; U. Baltensperger (Atmospheric Chemistry and Physics, 2011)
Fourteen years of meteorological parameters, aerosol variables (absorption and scattering coefficients, aerosol number concentration) and trace gases (CO, NOx, SO2) measured at the Jungfraujoch (JFJ, 3580 m a.s.l.) have been analyzed as a function of different synoptic weather types. The Schüepp synoptic weather type of the Alps (SYNALP) classification from the Alpine Weather Statistics (AWS) was used to define the synoptic meteorology over the whole Swiss region. The seasonal contribution of each synoptic weather type to the aerosol concentration was deduced from the aerosol annual cycles while the planetary boundary layer (PBL) influence was estimated by means of the diurnal cycles. Since aerosols are scavenged by precipitation, the diurnal cycle of the CO concentration was also used to identify polluted air masses. SO2 and NOx concentrations were used as precursor tracers for new particle formation and growth, respectively. The aerosol optical parameters and number concentration show elevated loadings during advective weather types during the December–March period and for the convective anticyclonic and convective indifferent weather types during the April–September period. This study confirms the consensus view that the JFJ is mainly influenced by the free troposphere during winter and by injection of air parcels from the PBL during summer. A more detailed picture is, however, drawn where the JFJ is completely influenced by free tropospheric air masses in winter during advective weather types and largely influenced by the PBL also during the night in summer during the subsidence weather type. Between these two extreme situations, the PBL influence at the JFJ depends on both the time of year and the synoptic weather type. The fraction of PBL air transported to the JFJ was estimated by the relative increase of the specific humidity and CO.